2016
DOI: 10.1371/journal.pone.0151173
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Antiviral Signalling by Single Nucleotide Polymorphisms (SNPs) of Mitochondrial Antiviral Signalling Protein (MAVS)

Abstract: Genetic variation is associated with diseases. As a type of genetic variation occurring with certain regularity and frequency, the single nucleotide polymorphism (SNP) is attracting more and more attention because of its great value for research and real-life application. Mitochondrial antiviral signalling protein (MAVS) acts as a common adaptor molecule for retinoic acid-inducible gene-I (RIG-I)-like receptors (RLRs), which can recognize foreign RNA, including viral RNA, leading to the induction of type I int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Polymorphisms at the IPS1 locus are linked to type-I IFN deficiency in man and may therefore underlie susceptibility to viral infections 16 . Here, we questioned whether an interaction between IPS-1 deficiency and respiratory viral infection might underpin the association between attenuated IFN responses, severe bronchiolitis and subsequent development of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms at the IPS1 locus are linked to type-I IFN deficiency in man and may therefore underlie susceptibility to viral infections 16 . Here, we questioned whether an interaction between IPS-1 deficiency and respiratory viral infection might underpin the association between attenuated IFN responses, severe bronchiolitis and subsequent development of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the C79F MAVS SNP leads to a MAVS loss-of-function mutation by impairing MAVS-tumor necrosis factor receptor-associated factor 3 interaction, Female Female Female Female Female Female Passage 2 2 2 2 2 2 Total SLEDAI score 6 6 2 7 0 2 Anti-RNP, AI (normal 0.0-0.9) and this mutation is more frequent in individuals of African origin (32). Therefore, the genomic samples from SLE patients were genotyped at the rs11905552 site in the MAVS gene for the C79F MAVS SNP (29). No C79F MAVS SNP was found in the SLE patients in this study (data not shown), ruling out the possibility that the MAVS loss-of-function mutation could have contributed to the phenotypes observed in the present work.…”
Section: Sle Bm-mscs Display Msc Markers Andmentioning
confidence: 99%
“…We found that the heterozygous genotype (CA) in MAVS rs6052130 was significantly associated with an increased risk of cervical precancerous lesions. Previous studies have confirmed that SNPs in MAVS exerted inhibitory effects on antiviral signaling in response to dsRNA (42). In addition, Lad and colleagues (43) found the splicing variants of MAVS, MAVS 1a, inhibits RIG-I and MAVS activity.…”
Section: Discussionmentioning
confidence: 85%
“…Our functional analysis in PBMCs showed that the MAVS rs6052130 CA or AA genotype might downregulate the production of IFNb, although a significant difference of MAVS mRNA expression in different rs6052130 genotypes was not observed. Therefore, we speculated that the rs6052130 variant in the MAVS gene might contribute to dislocation of MAVS from the outer mitochondria membrane (42), which may lead to loss of RLR antiviral signaling in response to HPV, thereby promoting evasion of HPV, leading to a more robust infection and ultimately contributing to an increased risk of cervical precancerous lesions. More studies are warranted to elucidate these speculations.…”
Section: Discussionmentioning
confidence: 99%